Release of ammonia from conventional power plant fly ash after the introduction of SNCR process - Beranová, Denisa; Opravil, Tomáš; Ptáček, Petr; Snop, Roman (IOP Publishing, 2018)
The paper deals with a study of various factors affecting the release of ammonia from conventional power plant fly ash after introduction of SNCR (Selective non-catalytic reduction). SNCR is a method of flue gas denitrification based on the chemical reduction of nitrogen oxide into nitrogen and water vapour. Reduction has many by-products, various ammonia salts, which could contaminate fly ash and deteriorate its properties and application. The chemical and phase composition of fly ash was determined by X-Ray Fluorescence and X-Ray Diffraction. To predict the contaminated fly ash behaviour, the samples of fly ash with known ammonia content was prepared by mixing fly ash with exact amount of ammonia hydrogensulfate. Tests were performed on the samples prepared from contaminated fly ash as it was, contaminated fly ash with deionized water and as a mixture of contaminated fly ash, lime, gypsum and water (further stabilizate). Effects of various storage and mixing conditions on prepared samples properties were studied.

The paper deals with a study of various factors affecting the release of ammonia from conventional power plant fly ash after introduction of SNCR (Selective non-catalytic reduction). SNCR is a method of flue gas denitrification based on the chemical reduction of nitrogen oxide into nitrogen and water vapour. Reduction has many by-products, various ammonia salts, which could contaminate fly ash and deteriorate its properties and application. The chemical and phase composition of fly ash was determined by X-Ray Fluorescence and X-Ray Diffraction. To predict the contaminated fly ash behaviour, the samples of fly ash with known ammonia content was prepared by mixing fly ash with exact amount of ammonia hydrogensulfate. Tests were performed on the samples prepared from contaminated fly ash as it was, contaminated fly ash with deionized water and as a mixture of contaminated fly ash, lime, gypsum and water (further stabilizate). Effects of various storage and mixing conditions on prepared samples properties were studied.
Release of ammonia from conventional power plant fly ash after the introduction of SNCR process
Keywords: conventional power plant fly ash; SNCR; release of ammonia; conventional power plant fly ash; SNCR; release of ammonia